1982
DOI: 10.1111/j.1751-1097.1982.tb04389.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Light: Photosensitivity and Other Effects on the Visual System *

Abstract: It is generally stated in elementary lectures on sensory systems that the limits of the visible spectrum are 400 nm (violet) and 700 nm (red), although there are several exceptions to this generalization. Recently, the properties of ultraviolet (UV) vision in invertebrates, as well as vertebrates, have been better characterized, and it is worthwhile to examine visual phenomena in the UV region of the spectrum. The purpose of this review is to integrate what is known about UV vision in invertebrates, which have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 111 publications
1
35
0
1
Order By: Relevance
“…2A). In complementary experiments carried out in the laboratory, we (18,21), fishes (22), birds (23,24), and rodents (25) present visual sensitivity to UV radiation. However, photoreceptor sensitivity curves always have maxima in the UVA region (above 320 nm) (17-19, 21-23, 25), and it would seem unlikely, therefore, that these photoreceptors may detect variations in natural UVB levels.…”
Section: Resultsmentioning
confidence: 99%
“…2A). In complementary experiments carried out in the laboratory, we (18,21), fishes (22), birds (23,24), and rodents (25) present visual sensitivity to UV radiation. However, photoreceptor sensitivity curves always have maxima in the UVA region (above 320 nm) (17-19, 21-23, 25), and it would seem unlikely, therefore, that these photoreceptors may detect variations in natural UVB levels.…”
Section: Resultsmentioning
confidence: 99%
“…Many species have been credited with sensitivity to UV light (see Stark & Tan, 1982, for a review), and UV-sensitive photoreceptors have been identified by microspectrophotometry in several species of fish (see for example Bowmaker & Kunz, 1987). We report here the first electrophysiological recordings of UV-sensitive photoreceptors in a vertebrate, and confirm that absorption in the UV range is indeed physiologically relevant, rather than (for example) representing absorption by the 11-cis or all-trans isomers of free retinal.…”
Section: Spectral Sensitivitymentioning
confidence: 99%
“…bleaching events) within a given time period. The photosensitivity of rhodopsin to bleaching by UVA light is not known but rhodopsin absorbs UVA light as a result of its ' cis ' peak at 354 nm which absorbs at about one-third its primary peak (Stark and Tan, 1982). Furthermore, transmittance through the rat lens in the UVA ranges from 35 to 79 % between 325 and 400 nm which is much greater than in primates (Gorgels and van Norren, 1991).…”
Section: Discussionmentioning
confidence: 98%